A educação matemática: breve histórico, ações implementadas e questões sobre sua disciplinarização - Miguel, Antonio; Garnica, Antonio Vicente Marafioti [UNESP]; Igliori, Sonia Barbosa Camargo; D'ambrósio, Ubiratan (ANPEd - Associação Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
This text was elaborated in autonomous topics in order to discuss the configuration of mathematical education as an area of research and, in a historical panorama, explains and analyses how the efforts for its consolidation in Brazil have been effectively implemented. Starting from a presentation of some elements related to the emergence and organisation of research in mathematical education within an international perspective (D'Ambrósio), it goes on to sketch in the motivations and difficulties which led to the creation of a specific working group in mathematical education within ANPEd (Igliori). Finally, Miguel and Garnica discuss the implementation of mathematical education as a discipline from different theoretical perspectives. There are, then, four different views and voices, at times finely tuned and, at others, discordant which arise rooted in that space which the authors with their discourses, desire to see consolidated - mathematical education.

Este trabalho foi elaborado em tópicos autônomos para discutir a configuração da educação matemática como área de pesquisa e, num panorama histórico, expõe e analisa como têm sido implementados, efetivamente, esforços para sua consolidação no Brasil. A partir da apresentação de alguns elementos relativos à emergência e à organização da pesquisa em educação matemática no panorama internacional (D'Ambrósio), ele passa a esboçar as motivações e estrangulamentos que levaram à criação de um grupo de trabalho específico sobre educação matemática na ANPEd (Igliori). Miguel e Garnica, por fim, discutem, sob referenciais distintos, a disciplinarização da educação matemática. São, em resumo, quatro olhares e vozes que, ora em fina sintonia, ora em contraponto, surgem fincados no espaço que os autores desejam, com seus discursos, ver consolidado: a educação matemática.
Mathematical education: a brief history, actions adopted and questions on its formation as a discipline
Keywords: mathematical education; research; formation as a discipline; educação matemática; pesquisa; disciplinarização